Impact of Exports and Foreign Direct Investment on Gross Domestic Product in Sub-Sahara Africa - Antoine, Niyungeko (MEC-J (Management and Economics Journal), 2021)
ABSTRACTBhagwati developed a hypothesis that expected economic growth (EG) enhancing impact of exports (EXP) and foreign direct investment (FDI) interaction. This paper checks the validity of the Bhagwati hypothesis by examining the moderation and mediation effect of EXP in the relationship between FDI and Gross domestic product for Sub Sahara Africa countries (SSA) during 2018 period. To achieve the article purpose, normality test, robust regression, and causal analysis using bootstrapping procedure were performed using R programming environment. The correlation results revealed a strong correlation between FDI-EXP-GDP.Â  The coefficient of the robust regression of the interaction term of EXP and FDI was found positive, and statistically significant. The result of the mediation analysis showed that indirect relationship of FDI was found positive and significant whereas direct relationship was not significant.Â  The results are consistent with the previous studies, theory, and Bhagwati hypothesis. Theorical and practical implications were presented.